2014
DOI: 10.5740/jaoacint.sgeivarsen
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Chromatographic Isolation and Identification of Antibacterial Compounds from Artemisia annua L. That Inhibit Clostridium perfringens Growth

Abstract: Clostridium perfringens is the causative agent of necrotic enteritis leading to significant losses in the poultry industry. Dichloromethane and n-hexane extracts of aerial parts of Artemisia annua (Asteraceae) exhibited activity against C. perfringens with minimum inhibitory concentrations (MIC) of 185 and 270 μg/mL, respectively. Bioassay-guided fractionation of the extracts gave several active fractions (MIC between 75 and 600 μg/mL). Investigations of the most active fractions resulted in the isolation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Scoparone was previously isolated from A. scoparia [16][17][18][19][20][21] but was also found in some other species of this genus. Among others scoparone was found in A. capillaris, [22][23][24] A. annua, 25,26 and A. dracunculus. 27 Other abounded components in DE were nonacosane (5.9%), stigmasterol (4.9%), and tritriacontane (3.9%), while in EE scopoletin (1.2%) and vanillin derivatives (2.6%) were above threshold.…”
mentioning
confidence: 94%
“…Scoparone was previously isolated from A. scoparia [16][17][18][19][20][21] but was also found in some other species of this genus. Among others scoparone was found in A. capillaris, [22][23][24] A. annua, 25,26 and A. dracunculus. 27 Other abounded components in DE were nonacosane (5.9%), stigmasterol (4.9%), and tritriacontane (3.9%), while in EE scopoletin (1.2%) and vanillin derivatives (2.6%) were above threshold.…”
mentioning
confidence: 94%
“…A. annua is the most studied plant in the Artemisia genus. Ivarsen et al reported that dichloromethane and n-hexane extracts of the aerial parts of A. annua were active against C. perfringens with a MIC value of 185 and 270 µg/mL, respectively [ 10 ]. In addition, A. annua extracts have also been reported to inhibit a significant number of pathogens such as E. coli , S. typhi , B. subtilis , S. aureus , and C. perfringens [ 63 , 64 ].…”
Section: Anti-bacterial Properties Of the Artemisia ...mentioning
confidence: 99%
“…In addition, A. annua extracts have also been reported to inhibit a significant number of pathogens such as E. coli , S. typhi , B. subtilis , S. aureus , and C. perfringens [ 63 , 64 ]. The high anti-bacterial properties of A. annua are due to its primary compounds from essential oil including monoterpenoids group were 30.7% artemisia ketone (18) , 15.8% camphor (33) , and 18.2% from sesqueiterpenes [ 23 ] and also from sabinene ( 1 ), linalool ( 19 ), camphene ( 8 ), α-pinene ( 9 ), α-terpineol ( 24 ), borneol ( 31 & 32 ), camphor ( 33 ), eugenol ( 75 ), and coumarins [ 10 ]. The terpenoids (monoterpenoids) α-terpineol ( 24 ) is also found in A. feddei [ 13 ] and A. princeps Pamp [ 41 ] with a very low to very high activity against 20 pathogenic bacteria with a MIC value of 30 to 3200 µg/mL [ 13 , 41 ].…”
Section: Anti-bacterial Properties Of the Artemisia ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil of A. annua has an antipathogenic activity such as gram-positive, gram-negative bacterial strains and yeast strains and can interfere with the expression of cell-associated and soluble virulence factors [6]. There are several active fractions and components exhibiting activity against Clostridium perfringens with different minimum inhibitory concentrations [7]. A. annua L. extracts exhibit antimicrobial activity against the periodontopathic microorganisms Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum subsp.…”
mentioning
confidence: 99%